The case of the murderous Dr. Cream : the hunt for a Victorian era serial killer - Jobb, Dean, 1958- (Algonquin Books of Chapel Hill, 2021)
"Framed around one salacious trial in 1891 London, a fascinating and vividly told true-crime narrative about the hunt for one of the first known serial killers, whose poisoning spree in the US, Canada, and England coincided with the birth of forensic science as well as the public's growing appetite for crime fiction such as Sir Arthur Conan Doyle's Sherlock Holmes novels"--